A microporous cationic metal–organic framework for the efficient removal of dichromate and the selective adsorption of dyes from water. Issue 80 (2nd November 2017) - Guo, Mingming; Guo, Huadong; Liu, Siyu; Sun, Yingying; Guo, Xianmin
Abstract : A microporous anionic metal–organic framework has been synthesized, which can be used as the effective adsorbent to methyl orange and Cr2 O7 2− from aqueous solutions. Abstract : A unique microporous cationic metal–organic framework, namely [Cd(tipo)(HCOO)(H2 O)]·NO3 ·DMF (1 ), has been synthesized and structurally characterized [tipo = tris(4-(1 H -imidazol-1-yl)phosphine oxide)]. This compound exhibits rapid and selective separation of methyl orange. Meanwhile, it has also been developed as a potential adsorbent material for the efficient removal of Cr2 O7 2− from aqueous solutions with a high uptake of up to 228 mg g −1 .